Campath-1H therapy in refractory ocular inflammatory disease. Issue 1 (1st January 2000) - Dick, Andrew D; Meyer, Paul; James, Teife; Forrester, John V; Hale, Geoff; Waldmann, Herman; Isaacs, John D
Abstract : BACKGROUND: Standard therapy for severe, immune mediated, ocular inflammation has significant side effects, and may fail to control the disease. T cell directed monoclonal antibody (mAb) therapy can provide long term remission of inflammatory disease in experimental models. The Campath-1H mAb was administered to patients with severe, refractory, ocular inflammation. METHODS: 10 patients with severe, refractory, non-infectious ocular inflammatory disease were treated with Campath-1H mAb. This is a fully humanised mAb which recognises the pan-lymphocyte antigen CD52. RESULTS AND DISCUSSION: Following Campath-1H therapy, all 10 patients showed an initial resolution of their ocular symptoms and signs. Long lasting remissions were achieved in eight patients, in whom baseline immunosuppression could subsequently be reduced to minimal levels. The possible mechanisms of action of Campath-1H therapy are discussed.